Genre based Approach to Teach Writing Descriptive Text: Pendekatan Berbasis Genre untuk Mengajar Menulis Teks Deskriptif - Rusmawan, Putu Ngurah (JEES (Journal of English Educators Society), 2017)
This study aims to discuss how teaching and learning activities were carried out by using Genre based Approach in teaching writing descriptive text at junior high school. This study was conducted in the classroom of VII-1. Therefore, the appropriate design was qualitative research design. The subject of the study was the English teacher. To collect data, the researcher used observation and interview. The finding of the study described that the teaching and learning activities that were carried out by the teacher fulfilled the basic competencies. The teacher carried out the opening teaching activities by greeting, asking the students’ preparation during the lesson, checking the student’s attendance list, and informing the learning objective. The teacher carried out the main teaching activities by informing about how to write a descriptive text, giving, and asking opinions, eliciting the students’ understanding, prompting and directing to do exercises. The teacher carried out the closing teaching activities by directing the student to continue at home and eliciting the students’ reflection of what they could learn at that time.